A Mysterious Case of ST-Elevation Myocardial Infarction; an Old Man with Weight Loss and Dyspepsia - Morteza Safi; Isa Khaheshi; Mehdi Memaryan; Mohammadreza Naderian (Publisher: Shahid Beheshti University of Medical Sciences, 2017)
We present a 65-year-old man who developed retrosternal compressive chest pain. A 12-lead electrocardiography demonstrated ST-segment elevation in leads II, III and aVF. Emergent coronary angiography showed significant thrombus in the distal portion of the left main coronary artery. Abdomino-pelvic computed tomography scan, which was performed the next day, confirmed a pancreatic mass with peritoneal seedings, compatible with peritoneal carcinomatosis. This case underscores the importance of malignancies that may lead to a catastrophic ST-elevation myocardial infarction due to a hypercoagulable state and following thrombosis in the left main coronary artery.